A new species of African diurnal dwarf geckos (Gekkonidae: Lygodactylus) from the Lower Guinea rainforest - Röll, Beate; Pinto, Pedro Vaz; Lobón-Rovira, Javier (Zootaxa, 2024)
The genus Lygodactylus Gray is a species-rich group of small, diurnal geckos distributed in Africa, Madagascar, and South America. The genus is divided into several species groups based on morphological characters, biogeographical affinities and/or phylogenetic investigations. To date, some of these groups still contain candidate species. One of these candidate species, provisionally designed as L. sp. B (a single female from Cameroon), had been placed phylogenetically within the East African Lygodactylus scheffleri-group. Furthermore, it shares typical scale characters with all members of this group. However, L. fischeri Boulenger, eponym and member of the West/Central African L. fischeri-group, also shares these scale characters with the L. scheffleri-group and with L. sp. B. While it could be ruled out that L. sp. B was conspecific with any member of the L. scheffleri-group, it could not be ruled out that L. sp. B represents a female of L. fischeri, as there is no female type material nor a clear description of a female of L. fischeri. Only when a male of this taxon was discovered in Cabinda (Angola) in a case of barcoding, the problem could be solved. We here describe the female L. sp. B from Cameroon and the male from Cabinda as new species Lygodactylus lobeke sp. nov. It is a small nondescript species without any bold color markings, such as dark blotches above the shoulder and on the flanks, which mark the male L. fischeri. The male and the female do not differ in coloration. In captivity, the female showed distinct ‘mood dependent’ colorations, including a ‘pyjamas’ coloration. For phylogenetic analysis, only sequences of L. laterimaculatus Pasteur, L. gravis Pasteur and L. lobeke sp. nov. were available. Lygodactylus lobeke sp. nov. was recovered as an independent clade which differs greatly in 16S uncorrected pairwise distance (>10%) from these two congeners. The new species is known from two localities in the Lower Guinea rainforests, with a linear distance of about 850 km. Despite this great distance, both specimens of L. lobeke sp. nov. are genetically surprisingly similar (3.5%). Presumably, the species has a wide distribution within the Lower Guinea region and a continuous gene flow within the population.